DESAIN MEKANIK SISTEM PEMILAH SAMPAH PLASTIK OTOMATIS DI TEMPAT PEMBUANGAN AKHIR SAMPAH (TPA) - Rolan Siregar (Machine : Jurnal Teknik Mesin, 2022)
Plastic is a material that is widely used in modern society. You can see products made from plastic, ranging from toys, kitchen utensils, electronics to toothbrushes that are used every day. Plastics are widely used because of the advantages of plastic which is strong, lightweight, easy to form, is a good insulator, non-corrosive and durable. Currently, based on statistical data on Indonesia's domestic solid waste, plastic waste ranks second, namely 64 million tons per year or 14% of total waste production. This large consumption is not matched by the same amount of recycling. Plastic waste can cause problems for the environment because it is very difficult to decompose. The time to decompose plastic waste naturally takes approximately eighty years to completely degrade. Therefore, designing and making a plastic waste sorting tool that uses a waterwheel and koveyor working system, where later when this design has been applied and functions properly it can be useful for sorting plastic waste. When this tool is functional it will be very helpful in the environment of landfills and other places.